Contributions of Mathematical Modeling as a teaching method for deaf students - Ribas, Marcia Cristina (2018)
This article aims to highlight the contributions of Mathematical Modeling in pedagogical approaches with deaf students, in order to focus of inclusion, interaction, autonomy, and creativity, considering the question: what are the potentialities of Mathematical Modeling with deaf students in Basic Education? The actions were experience in classes, according to the steps proposed by Burak (2010). The pedagogical action totaled 33 hours, based on the "clothing making" theme. These activity was possible to note the appreciation of visual aspects, the participation of the students and research in which the teaching role assumed an orientation and collaboration character.